2014
DOI: 10.5902/1980509813325
|View full text |Cite
|
Sign up to set email alerts
|

Atividade alelopática de <i>Araucaria angustifolia</i> (Bertol.) Kuntze na germinação e crescimento inicial de <i>Lactuca sativa</i> L.

Abstract: RESUMOO presente estudo teve por objetivo avaliar as possíveis atividades alelopáticas de Araucaria angustifolia na germinação e crescimento inicial de Lactuca sativa. No experimento foram utilizadas sementes de alface e extrato aquoso extraído das folhas de araucária, com concentrações de 10%, 7,5%, 5,0% e 2,5%. O efeito destas quatro concentrações foi comparado com o de água destilada (concentração 0%). A partir dos dados coletados, determinou-se a percentagem de germinação (G%), índice de velocidade de germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
(4 reference statements)
2
7
0
4
Order By: Relevance
“…The results are similar to other studies, as reported by Silveira et al (2014), with aqueous extract of Araucaria angustifolia (Bertol.) Kuntze, which showed a decline in the length of the roots and stems at concentrations (25.0, 50.0, 75.0 and 100.0 g L -1 ) similar to those seen in this study.…”
Section: Resultssupporting
confidence: 82%
“…The results are similar to other studies, as reported by Silveira et al (2014), with aqueous extract of Araucaria angustifolia (Bertol.) Kuntze, which showed a decline in the length of the roots and stems at concentrations (25.0, 50.0, 75.0 and 100.0 g L -1 ) similar to those seen in this study.…”
Section: Resultssupporting
confidence: 82%
“…sativa, observou-se um decréscimo linear nos valores de porcentagem de germinação, ocasionando inibição em torno de 80% da germinação das sementes nas concentrações de 5,0% e 7,5% (m/v), o que pode ser explicado pela presença de componentes aleloquímicos (54) .…”
Section: Resultados E Discussõesunclassified
“…Regarding mean germination time and mean speed of germination, Silveira et al (2014) tested allelopathic activity of A. angustifólia on L. sativa. They found that aqueous extract from the Brazilian pine has inhibiting properties, thus showing allelopathic potential of this species.…”
Section: Resultsmentioning
confidence: 99%